2021
DOI: 10.3389/fnins.2021.645267
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Characterization of Pediatric Acute-Onset Neuropsychiatric Syndrome (PANS)

Abstract: IntroductionPANS is a controversial clinical entity, consisting of a complex constellation of psychiatric symptoms, adventitious changes, and expression of various serological alterations, likely sustained by an autoimmune/inflammatory disease. Detection of novel biomarkers of PANS is highly desirable for both diagnostic and therapeutic management of affected patients. Analysis of metabolites has proven useful in detecting biomarkers for other neuroimmune-psychiatric diseases. Here, we utilize the metabolomics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 85 publications
1
12
0
Order By: Relevance
“…Recently, in the research of markers for diagnosis, an alteration of plasma metabolic profile was observed in patients with PANS compared to healthy children, with regard to the metabolite levels associated with neurotransmission (glycine, tryptophan, histamine/histidine) and neuroinflammation (glutamine, 2-hydroxybutirate) ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in the research of markers for diagnosis, an alteration of plasma metabolic profile was observed in patients with PANS compared to healthy children, with regard to the metabolite levels associated with neurotransmission (glycine, tryptophan, histamine/histidine) and neuroinflammation (glutamine, 2-hydroxybutirate) ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the common and the specific metabolic features of ASD and PANS classes, we can summarize that asparagine and glycine appeared to be significantly decreased in both ASD and PANS sera and that impaired glucose metabolism appears to be a key feature of ASD, while a decreased tryptophan concentration, previously identified as a significant feature of metabolomic profile of PANS [ 18 ], was not observed in ASD subjects.…”
Section: Discussionmentioning
confidence: 74%
“…Blood samples (10 mL by venipuncture) were collected after an overnight fast (12 h) and centrifuged at 2500× g for 10 min at 4 °C. Sera, stored at −80 °C until analysis, were analysed as described in our previous study (Murgia et al, 2021) [ 18 ]. Details are reported in the Supplementary Materials .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between immune activation, neuroinflammation, and behavioral symptoms had been largely studied in the past two decades, especially in the pediatric autoimmune neuropsychiatric disorder associated with streptococcus (PANDAS)/pediatric acute-onset neuropsychiatric syndrome (PANS; Murphy et al, 2010 ; Swedo et al, 2015 , 2017 ; Zheng et al, 2020 ; Murgia et al, 2021 ). Some TS cases, considered as a putative example of such phenomenon, meet the criteria for PANDAS/PANS, suggesting that the two diseases may have similar etiological mechanisms in some specific situations ( Lamothe et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%